Peningkatan Pemahaman Terhadap Bahaya Rokok Elektrik Dan Vaping Pada Siswa Smp Al Falah Banyuwangi - Musyarofah, Atiqotul; Lestari, Sudarsri (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2023)
Community service activities ran smoothly and were welcomed by the school and students alike. This service activity was attended by 22 participants consisting of all class VII students of Al Falah Middle School in the Buluagung Village Hall Environment. Based on the analysis of the pre-test and post-test results, this service activity has been able to increase youth's knowledge and understanding of electric cigarettes and vaping and their dangers. This is important because by increasing their understanding and perception it is hoped that it will prevent youth from becoming new smokers or wanting to quit for those who are currently doing it. To prevent teenagers from spreading vaping and e-cigarettes, they need to be given correct information about e-cigarettes and their dangers. After the community service activities were carried out, teenagers at the Al Falah junior high school, showed a significant increase in knowledge after a post-test was carried out about the dangers of electric cigarettes and vaping. This is expected to prevent teenagers in the Tohpati banjar environment from being trapped in wrong perceptions about electric cigarettes and vaping and not becoming novice smokers or deciding to quit for those who are currently smoking or using e-cigarettes and vaping.